Anxiety-Like and Exploratory Behaviors of Isolation-Reared Mice in the Staircase Test - Yukio Ago; Keiko Takahashi; Shigeo Nakamura; Hitoshi Hashimoto; Akemichi Baba; Toshio Matsuda (Elsevier, 2007)
The behavior of isolation-reared mice has not yet been studied in the staircase test. The present study examined the effects of anxiolytic or anxiogenic agents and isolation rearing on the behavior of ddY (outbred) strain mice in the staircase test. Diazepam and phenobarbital increased the number of steps climbed, but did not affect rearing behavior in group-reared mice. FG-7142, a benzodiazepine inverse agonist, significantly increased the number of rearing with no changes in the number of steps climbed in group-reared mice. Methamphetamine increased the number of steps climbed and decreased the number of rearing in group-reared mice. Although isolation-reared mice showed hyperactivity, there was no difference in locomotor activity for the test period of 3 min between isolation- and group-reared mice. Under these conditions, isolation rearing increased the numbers of steps climbed and rearing compared to group-reared controls. Microanalysis of locomotor patterns of group-reared mice in the staircase test showed that anxiolytic drugs increased the number of climbing to the top step of the staircase and methamphetamine increased the number of climbing to the first to third step. These results suggest that isolation rearing causes an anxiety-like state with increased exploratory behavior in mice. Keywords:: staircase test (ddY strain mice), isolation rearing, locomotor activity, anxiety, exploratory behavior